Orbital period study of the Algol-type eclipsing binary system TW Draconis - Qian S.B. (2014)
The century-long times of light minimum of the Algol-type eclipsing binary star, TW Dra (BD + 64° 1077, Sp A5V+ K2III), are investigated by considering a new pattern of period change. Two sudden period increases and two successive period decreases are discovered to superimpose on a rapid secular increase (dP/dt =1 4.43 X 10-6 days/year). The secular increase may be caused by a dynamical mass transfer from the secondary to the primary component (dm /dt = 6.81 X 10-7 M⊙/year) that is in agreement with the semi-detached configuration of the system and with the existence of a hot spot and a gaseous stream in the binary system. The irregular period jumps superimposed on the secular increase can be explained by the structure variation of the K2-type giant via instabilities of the outer convective layer or via magnetic activity cycles. © 2002 Elsevier Science B.V. All rights reserved.